The New Economics of Semiconductor Manufacturing. - Christensen, C.M.
This article deals with the Toyota Production System that has been applied to integrated chip making. Even more important, Toyota's approach to mass production has produced bountiful profits. These early results point to the new economics of semiconductor manufacturing and that this will have a profound and lasting effect on the industry and create new opportunities for growth.
Keywords: Toyota Production System; Integrated chip making; Mass production; Semiconductor manufacturing economics